An uncommon cause of inappropriate ICD shock. Issue 6 (10th March 2020) - Bazoukis, George; Letsas, Konstantinos P.; Vlachos, Konstantinos; Tse, Gary; Manolatos, Dimitrios; Sideris, Antonios; Efremidis, Michael; Xydonas, Sotirios
Abstract: In cases of electromagnetic interference (EMI), if the source of the inappropriate EMI cannot be identified, then the sensitivity of the device could be decreased, or the cycle length of the VF detection trigger zone changed. Abstract : In cases of electromagnetic interference (EMI), if the source of the inappropriate EMI cannot be identified, then the sensitivity of the device could be decreased, or the cycle length of the VF detection trigger zone changed.